1997
DOI: 10.1063/1.120567
|View full text |Cite
|
Sign up to set email alerts
|

Observation of oxide/Si(001)-interface during layer-by-layer oxidation by scanning reflection electron microscopy

Abstract: We have found that terrace contrast of oxidized Si(001) substrate observed with a scanning reflection electron microscopy (SREM) is reversed by progress in thermal oxidation by one atomic layer of Si. The cause for such terrace contrast reversion is that reflection electron intensity depends on Si-bond direction at oxide/Si interface. This fact was confirmed by calculations based on a multiple scattering theory. The motion of oxide/Si-bulk interface can be, thus, observed by SREM. The reversion and continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Thus, in most cases the theoretical approaches have provided static equilibrium configurations, from which the growth kinetics could only be extracted in some specific cases. 5,6,8 So far, therefore, complications in the oxidation process have prevented quantitative understanding of silicon oxide formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in most cases the theoretical approaches have provided static equilibrium configurations, from which the growth kinetics could only be extracted in some specific cases. 5,6,8 So far, therefore, complications in the oxidation process have prevented quantitative understanding of silicon oxide formation.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases there is a need to control the very first interfacial layer of SiO x . Recognizing the limitation of highly successful continuum approaches such as the Deal-Grove model 2 in describing the growth of ultrathin films, researchers over the past decade have devoted considerable effort towards developing experimental techniques [2][3][4][5][6][7][8][9] and first principles calculations [10][11][12][13][14][15][16][17][18][19] in order to arrive at an atomic scale understanding of the initial oxide growth mechanism. Ab initio electronic structure calculations have proven very useful in determining the local initial oxidation configurations and associated energies, [10][11][12][13][14] while ab initio molecular dynamics simulations have been used to depict the interface structure starting from known crystalline structures and interface bonding.…”
Section: Introductionmentioning
confidence: 99%
“…However, at the atomic level, the oxidation mechanism is not yet completely understood. Recently, the layer-by-layer process model, where oxidation is modeled as a layer-by-layer process at the SiO 2 /Si interface, was proposed from the measurements of high-resolution transmission electron microscopy (TEM), scanning reflection electron microscopy (SREM), reflection high-energy electron diffraction, and X-ray photoelectron spectroscopy (XPS) [6][7][8][9][10][11][12][13][14][15][16]. In this study, we directly observed the morphology change of the SiO 2 /Si(111) interfaces of oxide films grown at different temperatures, 1050 and 900°C, with various thickness from 4 to 14 nm under near normal conditions where metal-oxidesemiconductor devices are fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation of the surfaces was carried out by introducing molecular oxygen into the analysis chamber. Since the electron gun and the energy analyzer were independently evacuated, the AES measurement could be performed under oxygen pressure on the order of 10 26 Torr.As we previously reported, since SREM images of SiO 2 ͞Si systems are obtained by recording the intensity change in reflection spots from a crystal Si substrate covered with an amorphous oxide layer, the interfacial structure can be observed without the need to remove the SiO 2 overlayer [12][13][14]. Figures 1(a)-1(d) show SREM images of Si(001) surfaces before and after oxidation.…”
mentioning
confidence: 95%